Islamic View of Human Nature towards Education - Septiana (Penerbit Hellow Pustaka, 2023)
Human existence begins with weakness and inability which will then move towards strength. Humans can easily take advantage of the grace and gifts bestowed upon them, but humans must fulfill an obligation to their God. Human dignity before God is not measured by how high their rank and position, their lineage, or their wealth. But when Allah is measured, it is his piety. Humans from the Islamic perspective will still be born in a state of fitrah, namely holy, clean, free from all sins, and have a tendency to accept religion, faith and monotheism. Whether humans become good or bad is a result of education and environmental factors, not their original character. According to Abd al-Rahman al-Bani, quoted by an-Nahlawi, the task of Islamic education is to safeguard and maintain the nature of students, then develop and prepare all the potential they have, by directing the existing nature and potential towards goodness and perfection, and realizing a the program in a more gradual manner. (Nahlawi, 1996) Development of human nature can be done through various learning activities. Namely through an institution. The development of human nature can be done through learning activities. Namely through various institutions. What is meant by unfocused learning is through education at school only, but can also be done outside school, either in the family, community or through existing social and religious institutions. From an Islamic point of view, fitrah is a natural innate tendency from birth. The creation of a creature for the first time is in a natural structure, one of which is human, human since the beginning of his birth has had an innate religion or belief that is passed down from his parents. Apart from being a religion of nature, Islam is also in accordance with human religious instincts and even supports the needs and development of nature.